Soil microbial and chemical responses to foliar Epichloë fungal infection in Lolium perenne, Hordeum brevisubulatum and Achnatherum inebrians. (October 2021) - Yang, Zhenhui; Jin, Yuanyuan; Hou, Fujiang; Bowatte, Saman
Abstract: We tested whether the host species identity in grass- Epichloë symbioses affected soil chemical and microbial properties. We grew endophyte infected (E+) and endophyte free (E−) Lolium perenne, Hordeum brevisubulatum and Achnatherum inebrians for 18 months in field plots. In E+ soil of all three grasses, available phosphorus was lower whereas total soil nitrogen was higher. Endophyte effects on soil pH, microbial biomass nitrogen, total carbon and organic carbon as well as bacteria and fungi abundance were host species dependent. Ammonia oxidizing bacteria abundance was higher in E+ soils for all species. Bacterial community composition of E+ and E− soils were different only for Lolium perenne with soil pH being the key factor. Fungal community composition of E+ and E− soils was not different for the three grasses. This study confirmed that the effects of foliar Epichloë infection on belowground properties depended on host species identity. Highlights: Foliar Epichloë infection (E+) affected soil properties differently between hosts. Soil available phosphorous was higher in foliar Epichloë infection free (E−) soils. Total nitrogen and ammonia oxidizing bacteria abundance were higher in E+ soils. Bacterial diversity differed between E+ and E− perennial ryegrass soils. Soil pH contributed the most to bacterial diversity variation.